Design of a new supersonic biplane. (October 2020) - Zhai, Jian; Zhang, Chen-An; Wang, Fa-Min; Zhang, Wei-Wei
Abstract: A classic Busemann biplane, consisting of two isosceles-triangle airfoils, can effectively reduce wave-drag and sonic boom in the design condition by correctly placing its lower and upper airfoils. However, its aerodynamic performance dramatically decreases in the off-design conditions due to the flow choking problem. This study presents a new supersonic biplane aiming to produce as low wave-drag as the Busemann biplane in the design condition and to weaken the flow choking problem in the off-design conditions. It places a flat-plate in the middle of the Busemann biplane and removes the upper isosceles-triangle airfoil, so it consists of an isosceles-triangle airfoil and a flat-plate. The design method defines the position between the isosceles-triangle airfoil and the flat-plate as well as the length of the flat-plate by the oblique shock function and Prandtl-Meyer function. In the design condition, the new supersonic biplane has the same wave-cancellation effect as the Busemann biplane. Besides, in the off-design conditions, it also has a weaker flow choking problem due to a higher ratio of the throat area to the inlet area. The numerical results show that it has lower drag, higher lift-to-drag ratio, and is easier to start than the Busemann biplane. Highlights: A new supersonic biplane is developed by replacing the upper airfoil of the Busemann biplane with a flat-plate. In the design condition, the new supersonic biplane has as low wave-drag as the Busemann biplane. In the off-design conditions, the new supersonic biplane has a weaker flow choking problem.